Pretreatment with Empty Liposomes Attenuates the Immunopathology of Invasive Pulmonary Aspergillosis in Corticosteroid-Immunosuppressed Mice - Lewis, Russell E. (American Society for Microbiology, 2007)
In a nonneutropenic murine model of invasive pulmonary aspergillosis, pretreatment with empty liposomes (E-lipo) was nearly as effective as 10 mg/kg of body weight liposomal amphotericin B and superior to 1 mg/kg amphotericin B deoxycholate. The beneficial immunomodulatory properties of E-lipo appear to compensate for their lack of direct antifungal activity.